KNOWLEDGE BUILDING ON ARCHITECTURAL CHARACTERISTICS OF PERANAKAN CHINESE HOUSE IN STRAITS SETTLEMENTS AND CHINATOWN OF YOGYAKARTA, INDONESIA: KETANDAN, PAJEKSAN, AND KRANGGAN - Thalita Kumala (Universitas Pendidikan Indonesia, 2022)
Chinese residing in various countries can strongly maintain their culture, shown in the form of a distinctive architectural identity. The principles of Chinese architecture certainly experience adaptation to various natural and cultural contexts of countries outside their home country, the four-seasons country, Mainland China. Current situation of Yogyakarta as a fast-growing tourism destination, diverse in cultures and nature is both an opportunity and threat towards Chinese housing established since 1755. In this research, the principles of Chinese architecture in their home countries will be studied, as a major influence of Chinese Peranakan Housing in Yogyakarta in order to understand and later on categorize each housing based on it’s architectural characteristics. Research methods are in stages, the first stage being literature review on typology and principles of Chinese architecture; the second stage is to structure and analyze the architectural characteristic findings; and the third stage is to draw conclusions from the process of interpretation, answering the research questions. The results are in the form of architectural characteristics derived from philosophy, principles, libation ritual, and kingship in early China to 1900s China.